MODEL DINAMIK FASE PERTUMBUHAN BUAH KELAPA - Yulinda, Yulinda; Jaya, A I; Ratianingsih, R (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2018)
Coconut (Cocos nucifera L.) is one of the Indonesian potential natural plant resources. Its fruit is a main part of the tree that plays an important role in raw materials industry. It is because the material could be processed to be a benefical various products. The diversity of the coconut fruit products leads to the importance of the study on coconut growth phase development. The model is expressed in a system of differential equation ð‘‘ð‘€ ð‘‘ð‘¡ = ð‘… âˆ’ ð›¼ð‘€ âˆ’ ðœ‡1ð‘€, ð‘‘ð‘ƒ ð‘‘ð‘¡ = ð›¼ð‘€ âˆ’ ðœ‡2ð‘ƒ âˆ’ ð›½ð‘ƒ, ð‘‘ð¶ ð‘‘ð‘¡ = ð›½ð‘ƒ âˆ’ ðœ‡3ð¶ âˆ’ Ïµð¶, ð‘‘ð‘€ð‘Ž ð‘‘ð‘¡ = ðœ–ð¶ âˆ’ ðœ‡4ð‘€ð‘Ž âˆ’ Î³ð‘€ð‘Ž, ð‘‘ð‘€ð‘  ð‘‘ð‘¡ = ð›¾ð‘€ð‘Ž âˆ’ ðœ‡5ð‘€ð‘  âˆ’ ðœŽð‘€ð‘ , ð‘‘ð‘€ð‘ ð‘‘ð‘¡ = ðœŽð‘€ð‘  âˆ’ ðœ‡6ð‘€ð‘ . The dinamic of coconut growth phase is studied by consider its stability at the critical point. The stability is determined using linearization method. The solution is analyzed both analitically and numerically. Simulated a stable endemic critical point indicates that the coconut production could be well prevent in each phase of growth